The Environmental Legal Framework of Mexican Caribbean Dunes: A Retrospective Case Study of Vegetation and Coastal Dune Loss in the Sian Ka’an Biosphere Reserve - Eloy Gayosso-Soto; Sergio Cohuo; Joan Alberto Sánchez-Sánchez; Laura Macario-González; Carmen Amelia Villegas-Sánchez; Alejandro Medina-Quej; Jorge Manuel Tello-Chan; Leopoldo Querubín Cutz-Pool; José Manuel Castro-Pérez (Land)
The Mexican Caribbean coastal dune is protected by national and international environmental legislation. However, through permits, concessions and authorizations for changes in land use, the coastal dune has been fragmented or suppressed, mainly for touristic activities, causing a decline in protective and ecological ecosystem services. In this study, we evaluated the strength and weakness of Mexican legislation to protect the Caribbean coastal dune ecosystem and estimated the historical and current effects on coastal dune vegetation and dune geomorphology, associated with legal allowances of land use change in the Sian Ka’an Biosphere Reserve (SKBR). Legislation at the federal, state and local level were critically reviewed, and with remote sensing techniques and the Remotely Piloted Aircraft System (RPAS), we conducted a case study in the SKBR to estimate coastal dune vegetation alteration trends during the period 2011–2020 and modifications on the dune geomorphology associated with land use change allowances. At the federal (four laws), state (eight laws) and local (nine Local and Territorial Planning Programs (POEL and POET) levels, we found a lack of consensus and alignment between regulations, starting with a lack of definition of ecosystems subject to protection. For coastal dunes, none of them consider topography, ecological function and a way to identify it in the field, making the surveillance highly complex and favoring land use changes, the removal of vegetation and dune geomorphology alteration. Remote sensing techniques showed that areas with land use authorizations exhibit negative vegetation cover trends (Mann–Kendall <−0.4), indicating a decline in vegetation cover density that is mostly anthropogenically induced. The RPAS analysis demonstrated drastic alterations to complete elimination of the coastal dune geomorphology in areas with land use change. In the Mexican Caribbean, the loss of coastal dune and associated ecosystem by the lack of congruent legislation threatens the environmental stability of the coastal areas.